AUTOMATED DESIGN OF LEATHER GOODS details BASED ON A RECTANGLE BY THEIR PARAMETERS - CHUPRYNKA, VIKTOR; NAUMENKO, BOGDAN; CHUPRYNKA, NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the work was to develop parametric models of leather goods details based on a rectangle according to the parameters of these details and to implement the obtained parametric models in a software product for automated design of leather goods details. To achieve this goal, parametric models of leather goods details were developed based on their parameters and the obtained parametric models were implemented in a software product. The work considers possible details of leather goods products based on a rectangle, namely: a rectangle, a rectangle with conjugate angles by an arc of a given radius, details that are a combination of a rectangle and a segment of a circle of a given height. For all these details, parameters were determined that allow for a unique description of these details. Parametric models of details were created based on these parameters. Parametric models of details will describe the outer contour of the detail according to its parameters. Since the external contours of most leather goods details cannot be described analytically, they were approximated using polygons with the required accuracy, i.e., for their unambiguous representation, we used piecewise linear approximation. For the parametric model of the part, the coordinates of each vertex of the approximating polygon for this part were determined through its parameters. The proposed parametric models of leather goods details based on a rectangle are implemented in the software product. This software product allows you to calculate the coordinates of the vertices on the external contour of the details, save this information in a file or print drawings of these details. The presented software product can be used in leather goods and other industries to design details based on a rectangle. The developed software product is easy to use and does not require much time to master.
Keywords: automated design; leather goods details; parametric models; software product